Proceedings of the Eighth West Lake International Conference on SMB : October 15-17 2006, Hangzhou, P.R China - Zhang, Henry; Zhao, Rui Mei; Chen, Lisa (Orient Academic Forum, 2006)
The focus of this conference was to seek, develop and share new and innovative small and medium enterprise ideas, research outcomes and strategies and policies in changing and volatile times. The conference had made this the emphasis, with a particular focus on creativity in SMB (Small and Medium Business).